Research on Safety and Static-Dynamic Legibility of Distressed Pavement - Chengyuan Mao; Yiming Bie; Yulong Pei; Weiwei Qi (Discrete Dynamics in Nature and Society)
In order to study the impacts of distressed pavement on driving safety, the drivers’ driving behavior and driving characteristics need to be analyzed. By analyzing the drivers’ characteristics, driving behavior’ and braking characteristics of vehicles, relation between static legibility distance of the distressed pavement under different driving conditions and dynamic legibility distance during driving is revealed via statistical analysis. The relation between vehicle speeds, braking performance, and the minimum safety legibility distance is developed. The recommended static legibility distances for different speed limits are proposed, which would be useful to improve the driving safety under adverse road conditions.